Literasi Tangkal Berita Bohong (Hoaks) Pada Anak Di Komunitas Mat Peci Ciliwung Jakarta - Sandy Allifiansyah; M. Fikri Akbar; Noprita Herari; Callista Agatha Maharani; Damar Nurdiantoro (JURNAL ABDIMAS DOSMA (JAD), 2026)
This community service activity aimed to improve digital literacy among children in the Mat Peci Ciliwung Community in Jakarta so they can recognize and resist hoaxes. The program was carried out through interactive socialization involving lecturers and students with a communicative, dialogic, and child-friendly approach. The material was delivered in simple language to ensure it could be easily understood by the participants, and was reinforced through discussion and question-and-answer sessions. The results showed that the children participated enthusiastically, responded actively to the questions, and began to understand the importance of verifying information before believing or sharing it. This activity indicates that early hoax-literacy socialization can serve as an initial strategy to build children's critical attitude toward digital information.